Electrochemical hydrogen storage in ZrCrNiPdx alloys - Ruiz, Fabricio Carlos (2010)
The consumption of rechargeable batteries at worldwide level has increased constantly inthe last years, mainly due to the use of portable devices such as cellular phones, digitalcameras, computers, music and video reproducers, etc. Nickel Metal Hydride (NiMH) isa rechargeable battery system widely used in these devices, also including the most ofelectrical and hybrid vehicles (EV and HEV). The study of hydride forming alloys isfundamental for its use as negative electrode component in NiMH batteries. In previousworks, the electrocatalytic effect of Pd element addition to the electrode, in powder formand by means of electroless technique, has been studied. In this work, AB2-type alloys arestudied, in which Pd is incorporated to the structure by re-melting inside an arc furnace.The base alloy composition is ZrCrNi, and the composition of the elaborated compounds isZrCrNiPdx (x ¼ 0.095 and 0.19). The effect of the composition modification on these materialson properties such as electrochemical discharge capacity, activation and high ratedischargeability (HRD) is analyzed.